Electrical Characterization of Si/ZnO Nanorod PN Heterojunction Diode - Sadia Muniza Faraz; Wakeel Shah; Naveed Ul Hassan Alvi; Omer Nur; Qamar Ul Wahab (Advances in Condensed Matter Physics)
The electrical characterization of p-Silicon (Si) and n-Zinc oxide (ZnO) nanorod heterojunction diode has been performed. ZnO nanorods were grown on p-Silicon substrate by the aqueous chemical growth (ACG) method. The SEM image revealed high density, vertically aligned hexagonal ZnO nanorods with an average height of about 1.2 μm. Electrical characterization of n-ZnO nanorods/p-Si heterojunction diode was done by current-voltage (I-V), capacitance-voltage (C-V), and conductance-voltage (G-V) measurements at room temperature. The heterojunction exhibited good electrical characteristics with diode-like rectifying behaviour with an ideality factor of 2.7, rectification factor of 52, and barrier height of 0.7 V. Energy band (EB) structure has been studied to investigate the factors responsible for small rectification factor. In order to investigate nonidealities, series resistance and distribution of interface state density (NSS) below the conduction band (CB) were extracted with the help of I-V and C-V and G-V measurements. The series resistances were found to be 0.70, 0.73, and 0.75 KΩ, and density distribution interface states from 8.38 × 1012 to 5.83 × 1011 eV−1 cm−2 were obtained from 0.01 eV to 0.55 eV below the conduction band.